RESEARCH OF THE DISTRIBUTION AND TRANSMISSION OF COVID-19 INFECTION - Ismailov K. Ya; Abdullaev I. K (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article analyzes the prevalence of COVID-19 infection among the urban and rural population, the age and sex of patients, the course of the disease depends on the person’s age, the presence of chronic diseases, outpatient and inpatient treatment, the prevalence of coronavirus, and also analyzes the relationship with the human factor.